Air pollution-derived PM2.5 impairs mitochondrial function in healthy and chronic obstructive pulmonary diseased human bronchial epithelial cells. (December 2018) - Leclercq, B.; Kluza, J.; Antherieu, S.; Sotty, J.; Alleman, L.Y.; Perdrix, E.; Loyens, A.; Coddeville, P.; Lo Guidice, J.-M.; Marchetti, P.; Garçon, G.
Abstract: In order to clarify whether the mitochondrial dysfunction is closely related to the cell homeostasis maintenance after particulate matter (PM2.5 ) exposure, oxidative, inflammatory, apoptotic and mitochondrial endpoints were carefully studied in human bronchial epithelial BEAS-2B, normal human bronchial epithelial (NHBE) and chronic obstructive pulmonary disease (COPD)-diseased human bronchial epithelial (DHBE) cells acutely or repeatedly exposed to air pollution-derived PM2.5 . Some modifications of the mitochondrial morphology were observed within all these cell models repeatedly exposed to the highest dose of PM2.5 . Dose- and exposure-dependent oxidative damages were reported in BEAS-2B, NHBE and particularly COPD-DHBE cells acutely or repeatedly exposed to PM2.5 . Nuclear factor erythroid 2-p45 related factor 2 ( NRF2 ) gene expression and binding activity, together with the mRNA levels of some NRF2 target genes, were directly related to the number of exposures for the lowest PM2.5 dose (i.e., 2 μg/cm 2 ), but, surprisingly, inversely related to the number of exposures for the highest dose (i.e., 10 μg/cm 2 ). There were dose- and exposure-dependent increases of both nuclear factor kappa-B (NF-κB) binding activity and NF-κB target cytokine secretion in BEAS-2B, NHBE and particularly COPD-DHBE cells exposed to PM2.5 . Mitochondrial ROS production, membrane potential depolarization, oxidative phosphorylation, and ATP production were significantly altered in all the cell models repeatedly exposed to the highest dose of PM2.5 . Collectively, our results indicate a cytosolic ROS overproduction, inducing oxidative damage and activating oxygen sensitive NRF2 and NF-k B signaling pathways for all the cell models acutely or repeatedly exposed to PM2.5 . However, one of the important highlight of our findings is that the prolonged and repeated exposure in BEAS-2B, NHBE and in particular sensible COPD-DHBE cells further caused an oxidative boost able to partially inactivate the NRF2 signaling pathway and to critically impair mitochondrial redox homeostasis, thereby producing a persistent mitochondrial dysfunction and a lowering cell energy supply. Graphical abstract: Image 1 Highlights: Better knowledge of the critical role of mitochondrion in PM2.5 -induced toxicity. Mitochondrial ROS overproduction activates NRF2 and NF-k B signaling pathways. Inactivated NRF2 signaling pathway impairs mitochondrial redox homeostasis. Abstract : PM2.5 -induced oxidative burst partially inactivates the NRF2 signaling pathway and critically impair mitochondrial redox homeostasis, thereby producing a persistent mitochondrial dysfunction and a lowering cell energy supply.